New Strategies for Novel Drugs: Antimicrobial Peptides Containing Ferrocene with Improved Antifungal and Antiplasmodial Biological Activity - Costa, Natalia C. S. [UNESP]; Santos-Filho, Norival A. [UNESP]; Piccoli, Julia P. [UNESP]; Fusco-Almeida, Ana M. [UNESP]; Santos, Claudia T. [UNESP]; de Souza, Juliana O.; Zanini, Camila L.; Aguiar, Anna Caroline C.; Oliva, Glaucius; Guido, Rafael V. C.; Cilli, Eduardo M. [UNESP] (Bentham Science Publishers, 2022)
Background: Fungal and parasitic diseases are global health problems, and the available treatments are becoming ineffective, mainly due to the emergence of resistant strains of pathogens. Furthermore, the drugs currently in use exhibit high toxicity and side effects. The scarcity of efficient treatments for fungal and parasitic diseases has motivated the search for new drug candidates, including antimicrobial peptides. The chemokine class RP1 peptide shows inhibitory activity against bacteria, viruses, cancer cells and parasites. In addition, the organometallic compound ferrocene showed antiparasitic activity. Objective: Study aimed to assess the effect of conjugation of the RP1 peptide with ferrocene in terms of its structure, biological activity against fungi and parasites and toxicity. Methods: Peptides and conjugates were synthesized using solid phase peptide synthesis (SPPS). The Fc-RP1 peptide showed antifungal and antimalarial activities with low toxicity in the U87 and HepG2 cell lines. Results: The mechanism of action of these peptides, analyzed by flow cytometry in the fungus Cryptococcus neoformans, was through membrane permeabilization, with an emphasis on the Fc-RP1 peptide that presented the highest rate of PI-positive cell marking. Conclusion: In conclusion, ferrocene conjugated to antimicrobial peptide RP1 is an attractive biomolecule for drug discovery against fungal and parasitic diseases.
Keywords: Antimicrobial peptide; bioconjugate; ferrocene; fungal; parasitic; RP1 peptide